An experimental study on dynamic response of polyurea coated metal plates under intense underwater impulsive loading. (November 2019) - Li, Ying; Chen, Zihao; Zhao, Tian; Cao, Xiaofei; Jiang, Yongbo; Xiao, Dengbao; Fang, Daining
Highlights: The deformation process of the polyurea coated aluminum plate under underwater impact was studied. With the increase of peak shock wave pressure, the polyurea coating had a significant effect on the plastic deformation of the polyurea coated aluminum plate, which was manifested as significant strain rate effect. The quantitative relationship between residual deflection of aluminum plate and polyurea coating thickness was given. Abstract: Polyurea coating provides a new method to improve the underwater shock resistance of ships. In this study, high-strength shock wave was loaded on the polyurea coated 6061 aluminum target plate through impact-type underwater shock wave loading device, and the dynamic deformation process was recorded by three-dimensional digital imaging correlation (DIC) method. Then, the influences of the shock wave peak, polyurea coating thickness and coating method were investigated. The experimental results confirmed that the underwater shock resistance performance of polyurea coated aluminum plate was improved as the peak of initial loading pulse and the polyurea coating thickness increased. In the meanwhile, it was found that under the same polyurea content, the underwater shock resistance of the aluminum plate with polyurea coated on the front surface was basically the same as that of the aluminum plate with polyurea coated on the rear surface, both of which were better than that of the aluminum plate with polyurea coated on both surfaces. Finally, the quantitative relationships of the residual deformation of the polyurea coated aluminum plate with the peak of initial loading pulse and the polyurea coating thickness were concluded.